Development of korean-russian interpreting textbook: mobile application - Toktarova, Zh. (Journal of Oriental Studies, 2020)
The purpose of this paper is to describe the results of a study on the need to create educational material for interpreting from Korean into Russian, as well as a mobile application for Android devices, which was created by the author. To do this, the author conducts a survey among 3-4 year students of the specialty “Translation and Interpreting (Korean language)” of Kazakh National University named after alFarabi and Kazakh University of International Relations and World Languages named after Abylai Khan. Based on a literature review and a survey, the main chapters of the application textbook and practical exercises were defined. The practical exercises in the application are aimed at developing the competence of interpreting among student, such as language competency (in two languages), intercultural competency, research competency, technological competency, thematic competency, transfer competency, service provision competency, and ethical competency. This application can be used by students both for self-study and as additional material in practical classes of interpreting. This research is significant in that it was the first to develop an application for learning interpreting from Korean, which takes into account the needs of students and motivates Russian-speaking students. Key words: interpreting, Korean, interpreting competencies, mobile app, exercises.